Competitiveness analysis in roses systems (Rosa sp) in a Mexican environment - Velázquez-Torres, Ana Luisa; Callejas-Juárez, Nicolás; Martínez-Castañeda, Francisco Ernesto (REVISTA TERRA LATINOAMERICANA, 2022)
Within the framework of foreign trade, f loriculture is one of the agricultural activities that produces more high-value crops, creates more direct and indirect jobs and, consequently, generates income. In this context, the present research work aims to analyze the competitiveness at private prices of cut rose plantations, located territorially in the towns of Tenancingo and Villa Guerrero, State of Mexico. Through work carried out in the f ield, information was obtained from the organization related to costs, income, socioeconomic and market indicators during March-May 2019; Likewise, a representative sample of producers from Tenancingo and the Association of Floriculturists of Villa Guerrero A.C., with more than 29 years of work as floriculturists, was taken. For the analysis of the results, a Policy Analysis Matrix was structured in order to estimate the income, costs and prof its at private prices. The results revealed that there is no difference in production costs or prof its between the national and international markets, since the use of the properties has been prof itable and competitive, in addition to the above, in both scenarios the internal factors of production represented more than 80% of the costs, including and excluding the cost of land and labor, which represented the largest part of the resources, followed by transportation expenses. Considering that the competitiveness of the systems was based on the use of labor that replaced technological and capitalization advances, it follows that the competitiveness and profitability for both systems is marginal.